HAK EX OFFICIO HAKIM DALAM KASUS CERAI - Fathurrohmah Fathurrohmah; Sadari sadari (SHAKHSIYAH BURHANIYAH: Jurnal Penelitian Hukum Islam, 2022)
This article is the result of library research. This research is included in normative legal research. This research discussion aims to explain the basis of Islamic law on the judge’s ex officio authority of Nganjuk Religioun Court judges in judgement talak-divorce cases, number: 2033/Pdt.G/2017/PA.Ngj. Researcher analysis data by maqāsid sharī'ah theory. The findings of this study are that the use of ex efficio rights of the Nganjuk Religioun Court which does not follow civil procedural law has a strong Islamic legal basis. This argument is based on the maqāsid sharī'ah shāṭibi theory. The benefits that are guarded by the judge are in accordance with the al Dharūriyyāt category, especially hifz al nafs, namely the maintenance of the soul. The benefit of Dharāriyyāt is shown through the first data that the wife is proven not to be given her rights by her husband before the divorce is decided, so the judge considers ex officio authority; second, maintaining the rights of the ex-wife after the divorce even though the wife (the respondent) did not file a reconvention in the trial. Keywords: judge’s ex officio authority, divorce-talak, sharia purpose.